Structured programming in assembly language for the IBM PC and PS/2 - Runnion, William C. (New York : PWS Pub. Co., 1995)
A revised and updated text (1st ed., 1988) that teaches structured assembly language programming while introducing computer organization. In this edition, the author explores the capabilities of 8088/8086, 80286, and 80386 assembly language instructions (for IBM PC, PS/2, and compatible machines) in detail, while updating his entire discussion to conform with Version 6.0 of the Microsoft Macro Assembler (MASM). Annotation c. Book News, Inc., Portland, OR (booknews.co
Microcomputers and the IBM Personal Computer -- Data definition and data transfer -- Integer arithmetic -- Control structures -- Procedures, sub-procedures, and macros -- Bit manipulation -- Multiple precision integer arithmetic using the carry flag -- Arrays and character strings -- Interrupts and input/output -- Recursion -- BCD operations -- Segment linking -- Two-dimensional arrays and text graphics -- Appendices: Instruction summary -- Pseudo-operations -- Pseudocode -- Input/output procedures -- ASCII character set -- Support software
System requirements for computer disk: IBM PC, PS/2, or compatibles; DOS 3.3 and above.
1
Keywords: IBM Personal Computer -- Programming; Assembler language (Computer program language); Structured programming